Topical steroid induced Cushing’s syndrome-a rare entity - Gopi, Manigandan; Seshadri, M. S. (International Journal of Research in Medical Sciences, 2022)
The topical steroid therapy is the commonest mode of treatment for Psoriasis. When the therapy is overused, it can cause unusual side effects like Cushing’s syndrome which is very rarely reported and we are reporting such a case. Treatment with maintenance dose of steroids is necessary based on basal cortisol levels to avert hypocortisolemic crisis in Cushing’s syndrome, however in some select asymptomatic cases maintenance dose of steroids can be withdrawn and only stress dose be given in spite of low basal serum cortisol. We managed such a case and it is reported because of its rarity in clinical practice. This can alert the clinicians to avoid prescribing steroids as maintenance dose for a long time in asymptomatic Cushing’s syndrome with low morning cortisol and thereby reducing the side effects of long-term steroids on them.